2020
DOI: 10.4103/jfmpc.jfmpc_247_20
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with strain among informal care providers of patients with traumatic brain injury in Malaysia

Abstract: Purpose: This study aims to investigate the level of strain and various influencing factors among informal care providers of traumatic brain injury (TBI) patients. Methods: A cross-sectional study was conducted in a single center in Malaysia via recruiting care providers of patients with TBI. The modified caregiver strain index (MCSI) questionnaires were utilized to ascertain the level of strain. The demographic data of informal care providers were also obtained. Indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Interestingly, we have found the behavior and affective symptoms within NPS each accounted for caregiver burden. These findings are consistent with previous research that has linked sudden behavior changes following TBI (e.g., apathy, irritability, appetite, disinhibition, and agitation) (Devi et al, 2020;Machamer et al, 2002), or affective symptoms (Bamatraf et al, 2020;Kaewphinit et al, 2022, Simpson et al, 2020 to a lack of immediate coping mechanisms for caregivers.…”
Section: Impact Of Nps On Caregiver Burden and Well-beingsupporting
confidence: 92%
“…Interestingly, we have found the behavior and affective symptoms within NPS each accounted for caregiver burden. These findings are consistent with previous research that has linked sudden behavior changes following TBI (e.g., apathy, irritability, appetite, disinhibition, and agitation) (Devi et al, 2020;Machamer et al, 2002), or affective symptoms (Bamatraf et al, 2020;Kaewphinit et al, 2022, Simpson et al, 2020 to a lack of immediate coping mechanisms for caregivers.…”
Section: Impact Of Nps On Caregiver Burden and Well-beingsupporting
confidence: 92%
“…This was more common in unmarried patients with moderate to severe injuries. Parents or immediate family members tend to shoulder the responsibility as primary caregivers for a long period of time [ 44 ]. Our study found that independent living either alone or with friends is an independent predictor of good functional outcome.…”
Section: Discussionmentioning
confidence: 99%